Physical properties and biocompatibility of UHMWPE-derived materials modified by synchrotron radiation; Journal of Materials Science: Materials in Medicine; Vol. 25, iss. 8 - Bykova Y. V.; Weinhardt V.; Kashkarova A. I.; Lebedev S. M. Sergey Mikhailovich; Baumbach T.; Pichugin V. F. Vladimir Fyodorovich; Zaytsev K. V.; Khlusov I. A. Igor Albertovich (2014, 2014)
Title screen